Disorder of Sex Development and Associated Anomalies: A Cytogenetic study - Pandey, Anushree; Mishra, Dewanshi; Kumar Verma, Rakesh; Rani, Archana; Kumar, Navneet; Singh, S. N.; Kumar, Sudhir (Journal of Neonatal Surgery, 2025)
The correct spatiotemporal order and coordination of mutually antagonistic activating and repressing elements are essential for normal sex development. These elements control the unipotent gonad's commitment to the binary pathways that control typical sex development. Usually, the Y chromosome's SRY gene sets off a series of biochemical processes that result in the development of male sex. The term "disorders of sex development" refers to a broad category of congenital illnesses that are linked to abnormal internal and external genital development. Generally speaking, these illnesses are ascribed to variations from the normal course of sex development. Chromosome, gonadal, and anatomic anomalies are some of the categories into which disorders of sex development can be divided. Novel genetic variations among DSD patients have been found using genomic methods like next-generation sequencing techniques and microarray investigations. Above all, patient care must be tailored to each patient, particularly when it comes to choices on sex of raising, surgery, hormone therapy, and the possibility of preserving fertility. Therefore, the present study was undertaken to study the disorder of sex development and associated anomalies.